2021
DOI: 10.1016/j.clnu.2020.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Individualized target fortification of breast milk with protein, carbohydrates, and fat for preterm infants: A double-blind randomized controlled trial

Abstract: Background & aims: In preterm infants, natural variation of breast milk composition makes it difficult to achieve recommended macronutrient intakes with standard fortification. Evidence suggests that nutritional deficiency induces poor postnatal growth. This study investigates impacts of target fortification on preterm growth and metabolism by adjusting breast milk macronutrients. Methods: This study was conducted as a single-centre, double-blind, randomized controlled trial for infants <30 gestational weeks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 32 publications
2
62
0
Order By: Relevance
“…Improving HM fortification by IHMF through the use of infrared technology and extra protein and energy supplementation may be one of the strategies to optimize the nutritional composition of HM to meet the nutritional needs of preterm infants, especially when DM is used. It was demonstrated that IHMF decreases the variability linked to HM content and safely optimizes protein and energy intake [19,21,49,50]. Premature infants fed with low macronutrient content HM benefit the most from IHMF, with improved growth outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Improving HM fortification by IHMF through the use of infrared technology and extra protein and energy supplementation may be one of the strategies to optimize the nutritional composition of HM to meet the nutritional needs of preterm infants, especially when DM is used. It was demonstrated that IHMF decreases the variability linked to HM content and safely optimizes protein and energy intake [19,21,49,50]. Premature infants fed with low macronutrient content HM benefit the most from IHMF, with improved growth outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary findings from a larger randomized controlled trial evaluating individualized target fortification in preterm infants suggest that individualized fortification improved intake of fat, protein, and carbohydrates compared with standard fortification. 9 Target fortification also increased caloric intake and improved growth outcomes, such as weight gain and growth velocity. The impact on growth was most pronounced in a subgroup of infants who received breast milk with a lower protein content than average (Fig.…”
mentioning
confidence: 99%
“…Instead, growth rates similar to intrauterine trajectories can be achieved by rapid increases in enteral feeding volume and by achieving full enteral nutrition within 5–7 days of birth even in extremely low gestational age neonates [ 48 , 49 ]. However, even if weight gain along intra-uterine trajectories is achieved, very preterm infants still show insufficient lean body mass growth and an increased fraction of body fat at term-equivalent age [ 52 , 53 ]. This can be interpreted as a lack of essential nutrients required to achieve parenchymal and muscle mass growth as in utero [ 54 ].…”
Section: Transition From Intravenous To Enteral Sourcesmentioning
confidence: 99%
“…In a recent review including 7 RCTs with a total of 521 participants, increased growth rates for weight, length and head circumference were found with moderate to low evidence following individualized compared to standard non-individualized fortification [ 35 ]. In 2021, a double-blind, randomized controlled trial was conducted in 103 preterm infants <30 weeks comparing standard versus targeted fortification with modular proteins, lipids, and carbohydrates [ 52 ]. The targeted fortification group had higher macronutrient intakes and higher average growth velocity across the first 21 days of intervention (21.2 ± 2.5 vs. 19.3 ± 2.4 g/kg/d).…”
Section: Fortificationmentioning
confidence: 99%
See 1 more Smart Citation